Kajian Produk Olahan Susu Fermentasi - Wardhani, Siti Asih; Haris, Helmi; Fanani, Muhammad Zainal (Jurnal Ilmiah Pangan Halal, 2023)
Milk is a common ingredient in food for humans. Important substances, particularly animal protein, can be found in milk. Because milk contains nearly all nutrients, it has a high nutritional value. However, lactose intolerance, a key component of milk, prevents some people from drinking it. As a result, it is hoped that fermented milk, a food processing technology that can convert lactose into lactic acid that can be absorbed by the intestines, will be developed so that people who are allergic to milk can take advantage of the nutritional benefits of milk by consuming fermented milk. Yoghurt and kefir are included in the fermented milk.